New species of the genus Ypsiloncyphon (Insecta: Coleoptera: Scirtidae: Scirtinae) - Yoshitomi, Hiroyuki (Zootaxa, 2015)
Twenty-eight new species of the genus Ypsiloncyphon are described from Southeast Asia. The new species described in this paper are as follows: Y. laosensis sp. n., Y. myanmarnus sp. n., Y. nomurai sp. n., Y. bifurcatus sp. n., Y. bicornutus sp. n., Y. borneensis sp. n., Y. brachytrigonium sp. n., Y. garoensis sp. n., Y. kedahensis sp. n., Y. prolongatus sp. n., Y. guamensis sp. n., Y. philippinensis sp. n., Y. panayensis sp. n., Y. chlorizanoides sp. n., Y. bicolor sp. n., Y. sumatranus sp. n., Y. acer sp. n., Y. nokrekensis sp. n., Y. boukali sp. n., Y. javanicus sp. n., Y. nepalensis sp. n., Y. wallacei sp. n., Y. gedensis sp. n., Y. teruhisai sp. n., Y. chiangmaiensis sp. n., Y. flexus sp. n., Y. lanigerus sp. n., and Y. cervus sp. n. Additional specimens of Ypsiloncyphon mendosus (Klausnitzer, 1980), Y. luteoapicalis (Ruta, 2007) and Y. micans (Klausnitzer, 1973) are recorded. Species group IV is newly proposed. A species list for the genus is given.